Fatty acid composition and gene expression involved in lipid metabolism from Nelore and Rubia Gallega x Nelore cattle - Adrielle M. Ferrinho; Fabio Luis Henrique; Gabriella Vespe de Moura; Taiane da Silva Martins; Julian Muñoz; Lenise F. Mueller; Pollyana Leite Matioli; Tamyres Rodrigues de Amorim; Alessandra Bridi; Mirele D. Poleti; Juliano Coelho da Silveira; João Negrão; et al. (Livestock Science, 2026)

Genetic association of productive traits, carcass measurements and age at first calving in the genetic evaluation of the Nellore breed - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C. I. Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
The aim was to evaluate the genetic association between sexual precocity and productive performance in Nellore cattle. Records of standardized body weights at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age, Longissimus Muscle Area (LMA), backfat thickness (BFT), and age at first calving (AFC) were used. The mixed linear model included the fixed effects of contemporary groups (composed of herd, year, and season of birth, as well as the animal’s sex), in addition to the random effects of direct additive genetic, maternal genetic (for W120 and W210), and maternal permanent environment. The variance components were estimated by the restricted maximum likelihood method. The obtained direct heritability estimates were 0.45, 0.49, 0.42, 0.40, 0.33, 0.19, and 0.08 for W120, W210, W365, W450, LMA, BFT, and AFC, respectively. The Spearman correlations of the animals’ breeding values between the weight development estimates were of a high order, and for the traits of backfat thickness and age at first calving, it was 0.27, indicating a relationship at older ages with the onset of the acceleration of adipogenesis. The genetic gain obtained in AFC (0.48 days) with the correlated response related to LMA and BFT was − 0.05 and − 0.19 days, respectively. The genetic correlations obtained between AFC and the weight development traits were positive, however negative with the carcass-associated traits, indicating that the offspring are reproductively precocious, yet lighter and with a greater finish of subcutaneous fat.

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Reaction norm models for the evaluation of reproductive and productive performance in Nellore cattle - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C.I Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
This study evaluated genotype × environment interactions (G×E) in Nellore cattle for growth, reproductive, and carcass traits using reaction norm models. We analyzed the records of body weight and scrotal circumference at 12 and 18 months. (W365, W450, SC365, SC450), as well as loin eye area (LEA) and subcutaneous fat thickness (SFT), from herds across different Brazilian states were analyzed. A hierarchical one-step reaction norm model was applied, including fixed effects of contemporary groups (herd, year and season of birth, and sex), cow age at calving as a covariate, and random effects for additive genetics, permanent environment, and residuals. Bayesian inference with Gibbs sampling was used to estimate posterior distributions.Sires were classified according to environmental sensitivity into four categories: extremely robust, robust, plastic, and extremely plastic. For most traits, over 90% of sires were classified as robust or extremely robust, indicating stability of ranking across environments. Exceptions were observed for SFT and SC365, where lower correlations between extreme environmental gradients suggested G×E effects. Heritability estimates ranged from 0.07 to 0.32 for body weights and reached up to 0.76 for fat thickness, with higher values observed under more favorable environmental conditions. .These findings underscore the utility of reaction norm models for identifying environmentally robust sires under the variability of tropical production systems, thereby supporting more accurate and efficient selection decisions in genetic improvement programs.

Effects of apples ( Malus domestica ) and their derivatives on metabolic conditions related to inflammation and oxidative stress and an overview of by-products use in food processing - Otávio Simões Girotto; Otávio Oliveira Furlan; Renato Cesar Moretti Junior; Ricardo de Alvares Goulart; Edgar Baldi Junior; Caroline Barbalho-Lamas; Lucas Fornari Laurindo; Sandra M. Barbalho (Critical Reviews in Food Science and Nutrition, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Exploring intergenerational differences in consumer acceptance of insects-fed farmed fish - M.T. Trentinaglia; M. Adler; M. Peri; L. Panzone; L. Baldi (Food Quality and Preference, 2024)

Exploring novel circulating biomarkers for liver cancer through extracellular vesicle characterization with infrared spectroscopy and plasmonics - R. Di Santo; F. Verdelli; B. Niccolini; S. Varca; A. del Gaudio; F. Di Giacinto; M. De Spirito; M. Pea; E. Giovine; A. Notargiacomo; M. Ortolani; A. Di Gaspare; et al. (Analytica Chimica Acta, 2024)

Effect of long-term compost fertilization on the distribution of organic carbon and nitrogen in soil aggregates - P. Gioacchini; E. Baldi; D. Montecchio; M. Mazzon; M. Quartieri; M. Toselli; C. Marzadori (CATENA, 2024)

Marine turtles as bio-indicators of plastic pollution in the eastern Mediterranean - Emily M. Duncan; Hasan Deniz Akbora; Patrizia Baldi; Damla Beton; Annette C. Broderick; Burak Ali Cicek; Charlotte Crowe-Harland; Sophie Davey; Tess DeSerisy; Wayne J. Fuller; Julia C. Haywood; Yu Jou Hsieh; et al. (Marine Pollution Bulletin, 2024)

Pesticide exposure in greenspaces: Comparing field measurement of dermal contamination with values predicted by registration models - L. de Graaf; M. Bresson; M. Boulanger; M. Bureau; Y. Lecluse; P. Lebailly; I. Baldi (Science of The Total Environment, 2024)

Moving from ecological impacts to social vulnerability in data-scarce places - Matías E. Mastrangelo; Sebastián H. Villarino; M. Ximena Sirimarco; Sebastián Aguiar; Germán Baldi; Lucas Enrico; Laura Huaranca; María Vallejos (Journal of Environmental Management, 2024)

Estimating genetic parameters of reproductive, carcass, and meat quality traits in Polled Nellore cattle - M. M. S. Mamede; G. J. M. Rosa; E. C. Eifert; F. B. Lopes; F. Baldi; M. F. Costa; R. D. Sainz; A. S. Carmo; A. S. Mascioli; C. U. Magnabosco (Tropical Animal Health and Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Arterial Stiffness as a Cardiovascular Risk Factor in Prostate Cancer Survivors: A Case–Control Study - Lynnette M. Jones; Rebekah Wilson; Lee Stoner; J. Chris Baldi (Journal of Science in Sport and Exercise, 2021)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Stealth invasions on the rise: rapid long-distance establishment of exotic pines in mountain grasslands of Argentina - Tomás Milani; Esteban G. Jobbágy; Martín A. Nuñez; M. Eugenia Ferrero; Germán Baldi; François P. Teste (Biological Invasions, 2020)

Social-Ecological Functional Types: Connecting People and Ecosystems in the Argentine Chaco - M. Vallejos; S. Aguiar; G. Baldi; M. E. Mastrángelo; F. Gallego; M. Pacheco-Romero; D. Alcaraz-Segura; J. M. Paruelo (Ecosystems, 2020)

Improved process conditions for increasing expression of MHC class II protein from a stable Drosophila S2 cell line - Xiao Shen; Danijel Dojcinovic; Lucia Baldi; David L. Hacker; Immanuel F. Luescher; Florian M. Wurm (Biotechnology Letters, 2018)

Nutritional evaluation of former food products (ex-food) intended for pig nutrition - C. Giromini; M. Ottoboni; M. Tretola; D. Marchis; D. Gottardo; V. Caprarulo; A. Baldi; L. Pinotti (Food Additives & Contaminants: Part A, 2017)

Genetic parameters and investigation of genotype × environment interactions in Nellore × Hereford crossbred for resistance to cattle ticks in different regions of Brazil - D. R. Ayres; R. J. Pereira; A. A. Boligon; F. Baldi; V. M. Roso; L. G. Albuquerque (Journal of Applied Genetics, 2015)

Biochemical characterization of some cyanobacterial strains from salt marshes of the Venice Lagoon - A. A. Sfriso; D. Marchetto; M. Gallo; F. Baldi (Journal of Applied Phycology, 2014)

Computer image analysis: an additional tool for the identification of processed poultry and mammal protein containing bones - L. Pinotti; T. Fearn; S. Gulalp; A. Campagnoli; M. Ottoboni; A. Baldi; F. Cheli; G. Savoini; V. Dell’Orto (Food Additives & Contaminants: Part A, 2013)

Reduced glutamine concentration improves protein production in growth-arrested CHO-DG44 and HEK-293E cells - Yashas Rajendra; Divor Kiseljak; Lucia Baldi; David L. Hacker; Florian M. Wurm (Biotechnology Letters, 2012)

The morphological evolution of the Sciara del Fuoco since 1868: reconstructing the effusive activity at Stromboli volcano - Maria Marsella; P. Baldi; M. Coltelli; M. Fabris (Bulletin of Volcanology, 2012)

Variations in Anarthrophyllum rigidum radial growth, NDVI and ecosystem productivity in the Patagonian shrubby steppes - Ana M. Srur; Ricardo Villalba; Germán Baldi (Plant Ecology, 2011)

TubeSpin bioreactor 50 for the high-density cultivation of Sf-9 insect cells in suspension - Qiuling Xie; Patrik O. Michel; Lucia Baldi; David L. Hacker; Xiaowei Zhang; Florian M. Wurm (Biotechnology Letters, 2011)

Glycemic control influences lung membrane diffusion and oxygen saturation in exercise-trained subjects with type 1 diabetes - Courtney M. Wheatley; James C. Baldi; Nicholas A. Cassuto; William T. Foxx-Lupo; Eric M. Snyder (European Journal of Applied Physiology, 2011)

Cold tolerance in cypress (Cupressus sempervirens L.): a physiological and molecular study - Paolo Baldi; Luca Pedron; Ari M. Hietala; Nicola La Porta (Tree Genetics & Genomes, 2011)

Hyperosmolarity enhances transient recombinant protein yield in Chinese hamster ovary cells - Xiaowei Zhang; Isabel Fernandez Garcia; Lucia Baldi; David L. Hacker; Florian M. Wurm (Biotechnology Letters, 2010)

A survey of dioxins (PCDDs and PCDFs) and dioxin-like PCBs in sheep and goat milk from Campania, Italy - M. Esposito; F.P. Serpe; S. Cavallo; R. Pellicanò; P. Gallo; G. Colarusso; R. D’ambrosio; L. Baldi; G. Iovane; L. Serpe (Food Additives & Contaminants Part B-Surveillance, 2010)

Evaluation the of PL-PG-PA system in relation to quality of bovine milk - L. Rossi; F. Galante; E. Fusi; M. Luini; V. Dell’Orto; A. Baldi (Veterinary Research Communications, 2009)

Differential composition of culture supernatants from wild-type Brucella abortus and its isogenic virB mutants - M. Victoria Delpino; Diego J. Comerci; Mary Ann Wagner; Michel Eschenbrenner; Cesar V. Mujer; Rodolfo A. Ugalde; Carlos A. Fossati; Pablo C. Baldi; Vito G. DelVecchio (Archives of Microbiology, 2009)

A hydrological onset and withdrawal index for the West African monsoon - G. A. Dalu; M. Gaetani; M. Baldi (Theoretical and Applied Climatology, 2009)

High precision photogrammetry for monitoring the evolution of the NW flank of Stromboli volcano during and after the 2002–2003 eruption - P. Baldi; M. Coltelli; M. Fabris; M. Marsella; P. Tommasi (Bulletin of Volcanology, 2008)

High-titer, serum-free production of adeno-associated virus vectors by polyethyleneimine-mediated plasmid transfection in mammalian suspension cells - Markus Hildinger; Lucia Baldi; Matthieu Stettler; Florian M. Wurm (Biotechnology Letters, 2007)

Influence of the sample collection method on salivary interleukin–6 levels in resting and post-exercise conditions - M. A. Minetto; M. Gazzoni; F. Lanfranco; M. Baldi; L. Saba; R. Pedrola; P. V. Komi; A. Rainoldi (European Journal of Applied Physiology, 2007)

Recombinant protein production by large-scale transient gene expression in mammalian cells: state of the art and future perspectives - Lucia Baldi; David L. Hacker; Myriam Adam; Florian M. Wurm (Biotechnology Letters, 2007)

Climate Change: Causes and Medium Range Perspectives - G. Maracchi; M. Baldi (Veterinary Research Communications, 2006)

Cyclo-oxygenase-2 (COX-2) inhibition reduces apoptosis in acute myocardial infarction - A. Abbate; F. Limana; M. C. Capogrossi; D. Santini; G. G. L. Biondi-Zoccai; S. Scarpa; A. Germani; S. Straino; A. Severino; F. Vasaturo; M. Campioni; G. Liuzzo; et al. (Apoptosis, 2006)

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage - M. Fornai; G. Natale; R. Colucci; M. Tuccori; G. Carazzina; L. Antonioli; S. Baldi; V. Lubrano; A. Abramo; C. Blandizzi; M. Del Tacca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Iron deficiency-induced changes in carbon fixation and leaf elemental composition of sugar beet (Beta vulgaris) plants - A. D. Rombolà; Y. Gogorcena; A. Larbi; F. Morales; E. Baldi; B. Marangoni; M. Tagliavini; J. Abadía (Plant and Soil, 2005)

Cloning and linkage mapping of resistance gene homologues in apple - P. Baldi; A. Patocchi; E. Zini; C. Toller; R. Velasco; M. Komjanc (Theoretical and Applied Genetics, 2004)

Monte Carlo Inversion of DInSAR Data for Dislocation Modeling: Application to the 1997 Umbria-Marche Seismic Sequence (Central Italy) - S. Stramondo; S. Santini; P. Baldi; M. Dragoni; A. Piombo; S. Salvi; G. Spada (Pure and Applied Geophysics, 2004)

The climatology of sea breezes on Sardinia - M. Furberg; D. G. Steyn; M. Baldi (International Journal of Climatology, 2002)
Hourly wind speed and direction data from 12 coastline stations on Sardinia, Italy, are analysed in order to characterize sea breezes in the region. A set of criteria based on the diurnal reversal of wind direction, and the thermal gradient necessary to drive the circulation, is used to identify sea breeze days. Statistics are presented that describe the occurrence, duration, and strength of the sea breezes. On a stationwide basis, sea breezes are most frequent in the summer months (May–August), when they appear on more than one‐third of the days. Sea breeze occurrence and duration are the greatest for the stations on the east coast of the island. The all‐station average sea breeze duration reaches a maximum of about 9 h in June. The strength of the sea breezes is roughly 3 m s −1 during summer months on average over all stations in the sample. An analysis of mean daily hodographs for the stations in the sample shows clearly the onshore–offshore nature of the sea breeze circulation, and the response of the sea breezes to the local coastline. Sea breezes are shown to develop simultaneously on all coasts of the island under appropriate synoptic conditions. Copyright © 2002 Royal Meteorological Society.

DM235 (sunifiram): a novel nootropic with potential as a cognitive enhancer - Ghelardini C.; Galeotti N.; Gualtieri F.; Romanelli M.; Bucherelli C.; Baldi E.; Bartolini A. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Chromosome regions and stress-related sequences involved in resistance to abiotic stress in Triticeae - Luigi Cattivelli; Paolo Baldi; Cristina Crosatti; Natale Di Fonzo; Primetta Faccioli; Maria Grossi; Anna M. Mastrangelo; Nicola Pecchioni; A. Michele Stanca (Plant Molecular Biology, 2002)

Field assessments of gene flow from transgenic to cultivated rice (Oryza sativa L.) using a herbicide resistance gene as tracer marker - J. Messeguer; C. Fogher; E. Guiderdoni; V. Marfà; M. M. Català; G. Baldi; E. Melé (Theoretical and Applied Genetics, 2001)

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)

On the Use of Bayesian Methods for Evaluating Compartmental Neural Models - Pierre Baldi; Michael C. Vanier; James M. Bower (Journal of Computational Neuroscience, 1998)